Workplace and Non‐workplace Pro‐environmental Behaviors: Empirical Evidence from Florida City Governments. (29th November 2018) - Azhar, Aisha; Yang, Kaifeng
Abstract: Public employees are expected to be good stewards of public resources and engage in pro‐environmental behaviors (PEBs). Using different categorizations of PEBs, this article examines whether public employees perform these PEBs in workplace and non‐workplace settings. The article further investigates how PEBs are influenced by salient characteristics of public organizations—that is, public service motivation (PSM) and civic participation categorized as civic engagement and cognitive engagement. Data were collected through a survey of public employees in two city governments in Florida. A structural equation model was employed to test the proposed model. Findings indicate that PSM has a positive influence on workplace PEBs and similar PEBs in the non‐workplace settings. Civic engagement has a positive influence on both workplace and non‐workplace PEBs. Barriers significantly moderate the effects of PSM and cognitive engagement on workplace and non‐workplace PEBs .